Geomorphological features in the compositional construction of manor parks. Upper Lielupe river region - Ziemeļniece, Aija (Landscape Architecture and Art, 2024)
Cultural heritage is one of the assets that shape a country’s image. Latvia’s cultural heritage exists regardless of the ambitions of the political powers that have swept over Latvia - the Bolsheviks, the Red Revolution, the two wars and the refugee exodus, collectivisation, land reclamation, biogas plants, wind farms, solar panel fields, etc. Cultural heritage continues to be threatened by the trends of globalisation and each individual’s perception of the comfort of their own living space. The challenge for cultural heritage in the future is to be able to live with the multiplicity of horizontal and vertical legislation at different levels, different hierarchies, without losing the essence of the heritage. The main hope and ambition is that the heritage itself will not be lost behind bureaucratic actions and texts (Dambis). Heritage is everywhere. Seeing it requires professional knowledge and experience. We cannot privatise heritage by planting trees and building where we want. The property may be only a few metres outside the legal protection zone. The visual expression of the rural landscape is very strong, but also fragile. The poorly designed farmstead with its apple orchard, outbuildings, huge sheds, etc. can obscure iconic views to the natural substrate. It is worth mentioning the interdisciplinary assessment involving several specialists. The development of the site in time and space also creates new infrastructure with new functional pressures - traffic, emissions, biological treatment plants, noise, service areas, etc. The focus should therefore be on the cultural landscape as a whole rather than on the individual site.